Proceedings of the 6th International Conference on Computational Methods in Structural Dynamics and Earthquake Engineering (COM 2017
DOI: 10.7712/120117.5631.18327
|View full text |Cite
|
Sign up to set email alerts
|

Shaking Table Testing of Cylindrical Steel Liquid Storage Tanks

Abstract: Abstract. This paper presents the experimental campaign carried out on cylindrical liquid storage steel tank specimens in CEA TAMARIS facility.Two geometries of tanks have been tested on a shaking table under seismic conditions. The broad tank specimen (diameter 3 m, height 0.9 m) was dedicated to the study of sloshing and potential uplifting during the seism. This specimen was unanchored on the table and free to lift or slide. The influence of a floating roof on sloshing has been studied. The slender specimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Substantial efforts have been made in developing simplified models of above-ground liquid storage tanks. 19,21 The seismic performance of structures depends on the ground motion intensity, as was also observed for storage tanks. 7,12,16,20 It is known that ground motion intensity at the site is, to some extent, affected by the site properties 23 Passeri et al 24 reported that the soil deposit properties affect the site response and the seismic action at the ground surface and thus, for example, at the structure foundation elevation.…”
Section: Introductionmentioning
confidence: 80%
See 4 more Smart Citations
“…Substantial efforts have been made in developing simplified models of above-ground liquid storage tanks. 19,21 The seismic performance of structures depends on the ground motion intensity, as was also observed for storage tanks. 7,12,16,20 It is known that ground motion intensity at the site is, to some extent, affected by the site properties 23 Passeri et al 24 reported that the soil deposit properties affect the site response and the seismic action at the ground surface and thus, for example, at the structure foundation elevation.…”
Section: Introductionmentioning
confidence: 80%
“…Few recent experimental studies have focussed on the stress distribution on the tank wall in above-ground liquid storage tanks. 18,19 Many researchers 12,13,20 studied above-ground liquid storage tanks using refined FE models. Their studies focussed on two models applied to the liquid domain: an arbitrary Lagrangian-Eulerian model 12 and an acoustic model.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations